THE EVOLUTION OF SOCIAL ECONOMIC LAW: A LITERATURE REVIEW OF HISTORICAL AND CONTEMPORARYDEVELOPMENTS - Arga Baskara; Febri Atikawati Wiseno Putri, Susilowardani, Asri Agustiwi, Desi Syamsiah (INTELIGENSIA MEDIA, 2025)
This research aims to examine the evolution of social economy law through a literature analysis covering historical and contemporary developments. Social economy law has undergone significant transformations from its inception focusing on the protection of labour rights and the creation of social safety nets, to its current role of having to accommodate the complex dynamics of the global economy. This study explores the key changes that have taken place in social economy regulation and policy from the 19th century to the present day, including the influence of globalisation, market liberalisation and technological advancement. The research findings show that social economy law continues to adapt to respond to new challenges such as the digital economy, gig economy, and environmental sustainability issues. As such, the evolution of social economy law reflects the need to create a responsive, inclusive, and sustainable policy framework in the face of dynamic social and economic developments